Jurnal Pengaruh Iklim Organisasi Dan Kepuasan Kerja Terhadap Kinerja Guru - Hasan, Muhamad Abduh Daulanil; Ma’shum, Sya’roni; Saprialman, Saprialman (Jurnal Ilmiah Wahana Pendidikan, 2023)
Organizational climate and job satisfaction is one of the factors that affect teacher performance. The high performance of teachers is related to the organizational climate and job satisfaction of teachers in carrying out their duties. The purpose of this study was to determine the effect of organizational climate on teachers, determine the effect of job satisfaction on teachers and determine the influence of organizational climate and job satisfaction on teacher performance. The method used in this study is a survey while the data collection is by questionnaires to teachers who are in the MAN 4 KARAWANG environment.